Factor Analysis of Behavioral Variables Affecting Budgetary Slack. - Onsi, Mohamed (The Accounting Review, 1973)
This article presents information on an empirical study using factor analysis to analyze the relationship between budgetary slack and managerial behavioral variables. The magnitude of slack over time depends on the profitability of the firm, its sales growth, and many other behavioral factors that will be explored later. It is assumed that the costs of a firm that is successful in the market place will, tend to rise because of the existence of budgetary slack. The existence of budgetary slack causes corporate profits to be less than optimum, since the estimated cost function is not minimum, in classical economic theory. Budgetary slack also functions as a mechanism to stabilize the organization's system response to wide variability in its environment. It is assumed that top management is not in a good position to determine and control the amount of slack due to the different technologies and peculiarities of each division and the submission of divisional budgets in total aggregates. The size of the organization and the centralization or decentralization of decision-making are two factors that may affect the validity of this assumption.